Evaluasi Kualitas Informasi Situs Web Pemerintah Kabupaten Cirebon - Chairunisa, Meutia; Prima, Yunita; Priyatna, Centurion Chandratama (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
In the development of the digital era as it is today, human life has undergone quite significant changes, especially in the aspect of seeking information. The presence of the internet can fulfill human needs for communication and obtaining information. One of the utilizations of the internet is through the existence of websites as information media. The Cirebon Regency Government with the domain https://cirebonkab.go.id/ also utilizes the website as the main media in providing public information services in accordance with Presidential Instruction (Inpres) Number 3 of 2003 regarding the Policy and National Strategy for E-Government Development. The purpose of this research is to evaluate the quality of information and provide recommendations to the Cirebon Regency Government. The research is conducted using a descriptive method with a qualitative approach. In this study, ten indicators of information quality proposed by Knight & Burn are used. The research results show that overall, the quality of information on the Cirebon Regency Government's website is quite good. However, some weaknesses are still found, particularly in menus with empty data and some information that has not been updated. The researcher suggests that empty data should be promptly filled, and information should be consistently updated to improve the quality of information on the Cirebon Regency Government's website.